PERANCANGAN ALAT BANTU MEMBILAS PAKAIAN DENGAN PENDEKATAN DESAIN INKLUSIF UNTUK MENGURANGI RISIKO CARPAL TUNNEL SYNDROME - Gabriella Nadya Anggia; Winta Adhitia Guspara; Christmastuti Nur (ATRIUM: Jurnal Arsitektur, 2017)
Title: Design of Rinsing Clothes Tools with Inclusive Design Approach to Reduce Carpal Tunnel Syndrome Risk Based on case studies at Panti Wreda Perandan Padudan, Gondokusuman, Yogyakarta, the fact that the clothes that are washed by the elderly is not completely clean. One clean indicator of the laundry is seen from the absence of detergent foam that makes the water become cloudy when rinsing clothes. Manual rinsing process requires the work of both hands that seek friction and pressure (i.e. to rubben) so that the soap water contained in the fabric can come out. The movement of the evaporating on rinsing has a tendency to inflict numbness even pain (i.e. carpal tunnel syndrome) if done at high intensity. The condition can deteriorate in long-lasting routines in the elderly. In the process of cassing, the elderly have limited hand grips in conducting activities that are made repeatedly. With this problem, it is necessary to design the tools to rinse the clothes so as to minimize the foam attached to the clothes until the result of a cleaner laundry and can reduce the risk of carpal tunnel syndrome. The design of this product utilizes a two-stage inclusion approach, which is research and design designing. The research phase uses ergonomics- based methods with observation and interview techniques. The design process that was used after obtaining the designs statement was SCAMPER. Through this method, the tool is produced to rinse the laundry cleaner without experiencing the pain in the hands.